A Serious Game About Hematology for Health Care Workers (SUPER HEMO): Development and Validation Study - Julien Perrin; Amélie Meeus; Julien Broseus; Pierre-Jean Morieux; Valentine Di Ceglie; Julien Gravoulet; Maud D'Aveni (JMIR Publications, 2023)
BackgroundComplete blood count (CBC) and hemostatic screening tests are among the most commonly prescribed blood tests worldwide. All health care workers (nurse practitioners, pharmacists, dentists, midwives, and physicians) are expected to correctly interpret the results in their daily practice. Currently, the undergraduate hematology curriculum consists predominantly of lecture-based teaching. Because hematology combines basic science (blood cells and hemostasis physiology) and clinical skills, students report that they do not easily master hematology with only lecture-based teaching. Having interviewed students at the University of Lorraine, we considered it necessary to develop new teaching approaches and methods. ObjectiveWe aimed to develop and validate a serious game about CBC analysis for health care students. Our primary objective was to help students perceive hematology as being a playful and easy topic and for them to feel truly involved in taking care of their patients by analyzing blood tests. We considered that this game-based approach would be attractive to students as an addition to the classic lecture-based approach and improve their knowledge and skills in hematology. MethodsWe developed an adventure game called SUPER HEMO, a video game in which the player assumes the role of a protagonist in an interactive story driven by exploration and problem-solving tests. Following validation with beta testing by a panel of volunteer students, we used a novel, integrated teaching approach. We added 1.5 hours of gaming to the standard curriculum for a small group of volunteer students. Physician and pharmacy students in their third year at a single French university were invited to attend this extracurricular course. Pregame and postgame tests and satisfaction surveys were immediately recorded. Final hematology exam results were analyzed. ResultsA total of 86 of 324 physician students (26.5%) and 67 of 115 pharmacy students (58%) opted to participate. Median scores on the pre- and posttests were 6 out of 10 versus 7 out of 10, respectively, for the physician students, (P<.001) and 7.5 out of 10 versus 8 out of 10, respectively, for the pharmacy students (P<.001). At the final hematology evaluation, physician students who played SUPER HEMO had a slightly better median score than those who did not: 13 out of 20 versus 12 out of 20, respectively (P=.002). Pharmacy students who played SUPER HEMO had a median score of 21.75 out of 30; this was not significantly different from pharmacy students who did not play SUPER HEMO (20/30; P=.12). Among the participants who answered the survey (n=143), more than 86% (123/143) believed they had strengthened their knowledge and nearly 80% (114/143) of them had fun. ConclusionsFeedback from this game session provided evidence to support the integration of interactive teaching methods in undergraduate hematology teaching. The development of SUPER HEMO is intended to be completed so that it can become a support tool for continuing education.